Lopharcha moriutii, sp. nov. and Polylopha cassiicola Liu & Kawabe (Lepidoptera, Tortricidae, Chlidanotinae, Polyorthini) from Thailand and Hong Kong - Nasu, Yoshitsugu (Zootaxa, 2006)
Lopharcha moriutii, sp. nov., is described from Thailand and Hong Kong; the genus is recorded from China for the first time. Polylopha cassiicola is recorded from Hong Kong. Adults and genitalia are illustrated.